Environmental Information Disclosure, Fiscal Decentralization, and Exports: Evidence From China - Fang, Ziwei; Li, Zhaohua; Tao, Shuang (Frontiers in Environmental Science, 2022)
We take the "Environmental Information Disclosure Measures (Trial)" implemented in China as a quasi-natural experiment and employ the difference-in-difference (DID) method to identify the impact of environmental information disclosure (EID) on local exports. Additionally, we further investigate the impact of fiscal decentralization on local governments' performance of this centrally mandated EID policy. Our results suggest that EID significantly hinders local exports and such inhibition effect exhibits obvious regional and stringency heterogeneity. Furthermore, the degree of fiscal decentralization is positively related to the enthusiasm of local governments in implementing EID policy, thus strengthening EID’s inhibitory impact on local exports. As for the mechanisms behind, we verify that EID activates "cost effect" and increase the cost of local pollution control. However, it can’t stimulate local innovation at the same time and "innovation effect" doesn’t work, which ultimately results in the decrease in local exports; For cities with a high degree of fiscal decentralization, local governments tend to actively implement the centrally-mandated environmental protection policy by increasing investments in environmental pollution control and stimulating the innovation vitality of local enterprises. But the benefits from the innovation improvement can’t fully offset the negative impact of the increase in environmental cost in the short term, local exports further reduce.